Synthesis and biochemical evaluation of benzoylbenzophenone thiosemicarbazone analogues as potent and selective inhibitors of cathepsin L. Issue 21 (1st November 2015) - Parker, Erica N.; Song, Jiangli; Kishore Kumar, G.D.; Odutola, Samuel O.; Chavarria, Gustavo E.; Charlton-Sevcik, Amanda K.; Strecker, Tracy E.; Barnes, Ashleigh L.; Sudhan, Dhivya R.; Wittenborn, Thomas R.; Siemann, Dietmar W.; Horsman, Michael R.; et al.
Graphical abstract: Abstract: Upregulation of cathepsin L in a variety of tumors and its ability to promote cancer cell invasion and migration through degradation of the extracellular matrix suggest that cathepsin L is a promising biological target for the development of anti-metastatic agents. Based on encouraging results from studies on benzophenone thiosemicarbazone cathepsin inhibitors, a series of fourteen benzoylbenzophenone thiosemicarbazone analogues were designed, synthesized, and evaluated for their inhibitory activity against cathepsins L and B. Thiosemicarbazone inhibitors 3-benzoylbenzophenone thiosemicarbazone1, 1, 3-bis(4-fluorobenzoyl)benzene thiosemicarbazone8, and 1, 3-bis(2-fluorobenzoyl)-5-bromobenzene thiosemicarbazone32 displayed the greatest potency against cathepsin L with low IC50 values of 9.9 nM, 14.4 nM, and 8.1 nM, respectively. The benzoylbenzophenone thiosemicarbazone analogues evaluated were selective in their inhibition of cathepsin L compared to cathepsin B. Thiosemicarbazone analogue32 inhibited invasion through Matrigel of MDA-MB-231 breast cancer cells by 70% at 10 μM. Thiosemicarbazone analogue8 significantly inhibited the invasive potential of PC-3ML prostate cancer cells by 92% at 5 μM. The most active cathepsin L inhibitors from this benzoylbenzophenone thiosemicarbazone series (1, 8, and32 ) displayed low cytotoxicity toward normal primary cells [in this case human umbilical vein endothelial cells (HUVECs)]. In an initial in vivo study, 3-benzoylbenzophenone thiosemicarbazone (1 ) was well-tolerated in a CDF1 mouse model bearing an implanted C3H mammary carcinoma, and showed efficacy in tumor growth delay. Low cytotoxicity, inhibition of cell invasion, and in vivo tolerability are desirable characteristics for anti-metastatic agents functioning through an inhibition of cathepsin L. Active members of this structurally diverse group of benzoylbenzophenone thiosemicarbazone cathepsin L inhibitors show promise as potential anti-metastatic, pre-clinical drug candidates.